SPATIAL PATTERN OF TROPICAL CYCLONE IN SOUTH INDONESIA DURING 1990-2023 - Nur, Agus Salim; Wibowo, Adi; Tampubolon, Stefanus Binoto; Supriatna, Supriatna, Department of Geography, Faculty of Mathematics and Natural Sciences, Universi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2024)
Tropical cyclones are one of the most destructive weather phenomena because they pose three main dangers: heavy rainfall, strong winds, and storm surge. The occurrence of tropical cyclones is expected to increase both in terms of intensity and geographical spread due to climate change. Indonesia, located around the equator with a low Coriolis force, was previously considered safe from tropical cyclones. This study aims to examine the spatial pattern of tropical cyclones in the southern part of Indonesia during the period from 1990 to 2023 to understand the extent to which tropical cyclones can occur near the equator. The analysis of tropical cyclone data was conducted using satellite imagery and the Dvorak analysis method. The dates and positions (latitude and longitude) were extracted using GIS. The results show that the spatial pattern of tropical cyclones in southern Indonesia between 1990 and 2023 indicates that cyclones are more prevalent in the eastern region of Indonesia (Indian Ocean south of Nusa Tenggara, Timor Sea, Sawu Sea, Arafura Sea, and the Gulf of Carpentaria). Out of a total of 217 tropical cyclones in southern Indonesia, 113 (52%) formed in the eastern region, while 104 (48%) developed in the western region (Indian Ocean southwest of Sumatra to south of Bali). Of the 217 tropical cyclones that formed in southern Indonesia, 44 occurred at latitudes ≤ 11° S, or within Indonesian territory, with 29 (66%) forming in the western region and 15 (34%) in the eastern region of Indonesia. The results conclude that the spatial pattern of tropical cyclones has been updated compared to the previous theory, which stated that Indonesia was a cyclone-free zone due to its location less than 10° from the equator.